A Systematic Review of Research Exploring Stakeholder Views on the Kindergarten-school Transition - Anita Fleisz-Gyurcsik (Journal of Studies in Education, 2024)
A smooth kindergarten-school transition is till problematic, even though it has been receiving attention from researchers as well as education professionals (e.g. Heckman, 2011). It is clear to everyone that children, kindergarten teachers, primary school teachers, and parents are all greatly affected by the kindergarten-school transition (e.g. Correia & Marques-Pinto, 2016). Therefore, the goal of my study is the systematic review of research exploring the kindergarten-school transition related views and opinions of the stakeholders. A search was conducted for English language studies that were published in peer reviewed journals between 1 January 2016 and 1 September 2020, in the ERIC, Scopus and the Web of Science databases. The expressions „kindergarten school transition”; „transition into primary school”; „transition to school”; „starting school”; „beliefs concerning school transition” were used as search terms. A total of 646 publications were identified, of which 21 complied with the inclusion criteria. Those papers were included that present such empirical work that explore the views and opinions of stakeholders regarding the kindergarten-school transition of normally developing children. The present review considers six aspects: (1) the country where data were collected; (2) the phase of transition when data were collected; (3) the issue of transition studied; (4) participants; (5) data collection methods; (6) main results. The review showed that numerous questions regarding the kindergarten-school transition are researched worldwide. My study can serve a basis for understanding the problems of starting school in different countries, as well as to formulate further research questions, and to design further research.